Peran Praktik Manajemen SDM Modern dalam Meningkatkan Motivasi dan Produktivitas Karyawan: (Studi pada Perusahaan Sektor Umum di Indonesia) - Asnawi Hidayat; Jaelani Jaelani; Sunarmi Sunarmi; Cheesya Siska Adhiati (Lembaga Pengembangan Kinerja Dosen, 2025)
Employee productivity is a strategic factor for companies in facing increasingly competitive business competition. Various studies show that modern human resource management (HR) practices have a significant effect on employee motivation and performance. This study aims to analyze the relationship between HR practices, work motivation, and productivity in public sector companies in Indonesia. The study used mixed methods by involving 180 respondents through surveys and in-depth interviews with HR practitioners. Quantitative analysis was performed using descriptive statistics, Pearson correlation, and linear regression. The results showed that work motivation was in the high category (mean = 4.12) and had a strong relationship with productivity (r = 0.71; p < 0.01). Qualitative findings identified the main obstacles to increasing motivation, namely low management support, limited training budgets, and suboptimal internal communication. This research emphasizes the importance of the role of strategic HR in creating a work environment that is able to increase employee motivation and productivity. This study contributes to strengthening the literature on Indonesian HR management and provides practical implications for companies in designing performance improvement interventions.